THE IDENTITY CONSTRUCTION THROUGH KINSHIP ADDRESS TERM IN MALANG (KOTA & KABUPATEN) - Maula, Qonita Camelia A. (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media)DO - 10.18860/aicollim.v2i1.1344, 2021)
This study investigates the identity construction seen from the lexicon shift of kinship address terms in  Kota  Malang and  Kabupaten  Malang. Aiming to unveil the progress of kinship development of father, mother, grandfather, and grandmother in a family to obtain the reflected identity of the society. The data was taken from 30 participants' terms to address their parents and grandparents and participants’ kids’ term of addressing their parents and grandparents. With a total of 240 data and divided into 60 data for each kindship address terms of father, mother, grandfather, and grandmother. The data analysis conceith uncovering the lexicon shift, tcomparingpare the lexicon used by participants and participants' kids. However, the discussion's result proves that lexicon shift exists on the parents address terms to obtain different, unique and higher prestige values. Another result shows the preservation of grandparents address terms. Several factors that influence the lexicon shift are the use of standard Indonesian or English, the appearance of religious terms, the modification of two language terms, and the modification of a single term. Furthermore, the kinship address terms reflect the higher identity that some of the participants want to achieve.